177k views
3 votes
Match the equations of parabolas with the x-intercepts of the parabolas. y = x2 + x − 12 y = x2 + 5x + 4 y = -2x2 + 11x + 8 y = -2x2 + 9x + 18 y = x2 − 5x − 24 y = -x2 + 5x + 14 (-2, 0), (7, 0) arrowRight (-4, 0), (3, 0) arrowRight (-4, 0), (-1, 0) arrowRight (-3, 0), (8, 0) arrowRight

1 Answer

6 votes

Explanation:

Match the equations of parabolas with the x-intercepts of the parabolas.

We find the x-intercept of the equations to match the points by putting y=0,

1)
y=x^2+x-12


x^2+x-12=0


x^2+4x-3x-12=0


x(x+4)-3(x+4)=0


(x+4)(x-3)=0


x=-4,3

The x-intercept points are (-4,0) and (3,0).

2)
y=x^2+5x+4


x^2+5x+4=0


x^2+4x+x+4=0


x(x+4)+1(x+4)=0


(x+4)(x+1)=0


x=-4,-1

The x-intercept points are (-4,0) and (-1,0).

3)
y=-2x^2+11x+8


-2x^2+11x+8=0


(x+0.65)(x-6.15)=0


x=-0.65,6.15

The x-intercept points are (-0.65,0) and (6.15,0).

4)
y=-2x^2+9x+18


-2x^2+9x+18=0


(x+1.5)(x-6)=0


x=-1.5,6

The x-intercept points are (-1.5,0) and (6,0).

5)
y=x^2-5x-24


x^2-5x-24=0


x^2-8x+3x-24=0


x(x-8)+3(x-8)=0


(x-8)(x+3)=0


x=8,-3

The x-intercept points are (8,0) and (-3,0).

6)
y=-x^2+5x+14


-x^2+5x+14=0


-x^2+7x-2x+14=0


x(-x+7)+2(-x+7)=0


(x+2)(-x+7)=0


x=-2,7

The x-intercept points are (-2,0) and (7,0).

User Walfrat
by
5.8k points